Reliable Multicast in Heterogeneous Mobile Ad-hoc Networks - Begerow, Peggy; Schellenberg, Sebastian; Seitz, Jochen; Finke, Thomas; Schroeder, Juergen (Electronic Communications of the EASST, 2013)
In disaster scenarios, communication infrastructure could be damaged or completely failed. Mobile Ad-hoc Networks (MANETs) can be used to substitute failed communication devices and thus to enable communication. As group communication is an important part in disaster scenarios, multicast will be used to address several nodes. In this paper, we propose our new reliable multicast protocol RMDA (Reliable Multicast over Delay Tolerant Mobile Ad hoc Networks). We introduce an efficient group management approach and a new method for reliable multicast delivery over Delay Tolerant Networks. We show, that our protocol is adaptive to different kinds of MANETs, e.g. with or without clusterheads, respectively. For those without, we use our name resolution over adaptive routing approach.